Adverse events following emergent prehospital sedation of patients with behavioral emergencies: A retrospective cohort study - Lawrence H. Brown; Remle P. Crowe; Paul E. Pepe; Melissa L. Miller; Brooke L. Watanabe; Samuel S. Kordik; David A. Wampler; David I. Page; Antonio R. Fernandez; Scott S. Bourn; J. Brent Myers (Elsevier, 2022)
Summary: Background: Patients presenting to emergency medical services (EMS) with behavioral emergencies may require emergent sedation to facilitate care, but concerns about sedation-related adverse events (AEs) exist. This study aimed to describe the frequency of AEs following emergent prehospital sedation with three types of sedative agents: ketamine, benzodiazepines and antipsychotics. Methods: This retrospective cohort study included patients ≥ 15 years who presented to 1031U.S. EMS agencies in calendar year 2019 with behavioral emergencies necessitating emergent prehospital sedation. Serious AEs (SAE) included cardiac arrest, invasive airway placement, and severe oxygen desaturation (<75%). Less-serious AEs included positive pressure ventilation, any oxygen desaturation (<90%), oropharyngeal or nasopharyngeal airway placement, and suctioning. The need for additional sedation was also assessed. Findings: Of 7973 patients, 1996 received ketamine; 4137 received a benzodiazepine; 1532 received an antipsychotic agent; and 308 received an indeterminant agent. Cardiac arrest occurred in 11 patients (0·1%) and any SAE occurred in 165 patients (2·1%). Invasive airway placement was more frequent with ketamine (40, 2·0%) compared with benzodiazepines (17, 0·4%) or antipsychotics (3, 0·2%). Oxygen desaturation below 75% also occurred more frequently with ketamine (51, 2·6%) than with benzodiazepines (52, 1·3%) or antipsychotics (14, 0·9%). Patients sedated with ketamine were less likely to require additional sedation. Propensity-matching to minimize potential confounding between patient condition, sedative choice and AEs did not meaningfully alter the results. Interpretation: Although SAEs were rare among patients receiving emergent prehospital sedation, prehospital clinicians should remain mindful of the potential risks and monitor patients closely. Funding: None.